PENGARUH VARIABEL FUNDAMENTAL TERHADAP HARGA SAHAM - Rusli, Aditya (IQTISHODUNA, 2009)
Stock Exchange truly is a set of arrangement which enables long-term claim exchange, enables addition of financial assets (and debt) and at the same time, enables investor to always change and adjust his investment portfolio (through secondary market). For people in general, the existence of Stock Exchange can be an alternative choice of In this study, researcher used firm internal fundamental variables to test the relation of some fundamental variables on the price of stock. Internal fundamental variables like Price Earning Ratio, Price Book Price, Debt to Equity Ratio, Total Asset Turnover, Return on Investment, Return on Equity, Net Profit Margin, and Operating Profit Margin can be used as fundamental analysis variables that affect changes on stock price. Analysis model used was double regression model using 10 emitted mining companies’ stocks.The results of the study showed the existence of effect either all together or partially on fundamental variable against changes of stock price on go public mining companies in Jakarta Stock exchange (JSC). Of eight variables proposed; Price Earning Ratio, Return on Investment, Return on Equity, and Operating Profit Margin variables are variables that might affect stock price. Independent variables that affect stock price is Operating Profit Margin variables which means that mining sector can be a very prospective sector in the future if it is supported with good performance and good activities as well.